DEMOCRACY IN INTERNATIONAL LAW - Omar Mahmoud Almakhzoumi; Omar Mahmoud Almakhzoumi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
While the concept of democracy is an old concept at the internal level, it dates back to the ancient Greek society, meaning the rule of the people or the authority of the people. However, it is a modern concept at the international level. In light of the transformations witnessed by the world, and the aftermath of the Second World War and the aftermath of the Cold War and the bipolar war and the collapse of the Soviet Union, the idea of democracy was firmly established at the level of international law and became closely linked to the idea of human rights. Political and free and fair elections are a criterion for any democracy. International law requires respect for human rights and the use of elections; it permits the use of force to establish or restore democracy. Promising international law and democracy are the rules of international law implications.